Effects of angiotensin II blockade on the development of autoimmune thyroiditis in nonobese diabetic mice - Mori, Kouki (Clinical immunology (Orlando, Fla.), 2008)
We evaluated the effects of angiotensin II (Ang II) blockers, losartan, an Ang II receptor blocker, and enalapril, an angiotensin converting enzyme inhibitor, on the development of autoimmune thyroiditis in nonobese diabetic (NOD) mice, an animal model of Hashimoto's thyroiditis (HT). Mice were assigned into three groups, untreated, losartan-treated (30 mg/kg/day), and enalapril-treated (10 mg/kg/day) groups. Thyroiditis was induced by iodide ingestion (experiment 1) or mouse thyroglobulin (Tg) immunization (experiment 2). Both procedures effectively induced thyroiditis. While iodide ingestion failed to induce anti-mouse Tg antibody (TgAb) production, Tg immunization resulted in a significant increase in serum TgAb levels. In both experiments, neither losartan nor enalapril interfered with the development of thyroiditis and TgAb production. These results suggest that Ang II may not be associated with the development of autoimmune thyroiditis in NOD mice. Thus, the Ang II blockade may not have therapeutic potential in HT